School Heads Mobility: Lived Experiences and Effects on Leadership and Succession Program - Dollano, Marilyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of school heads regarding mobility and succession programs in the REINA District of Quezon Province, comprising the municipalities of Real, Infanta, and General Nakar. Anchored on the Transformational Leadership Theory, the study examined the effects of mobility on leadership continuity, school performance, stakeholder relationships, coping strategies, and leadership transitions. A qualitative transcendental phenomenological design was employed to understand the experiences of six school heads who had undergone three to five mobility assignments and had served as school heads for five to ten years. Data were collected through a researcher-made semi-structured interview guide that underwent validation and pilot testing. Individual interviews were conducted and analyzed using Colaizzi’s phenomenological method. The findings revealed that school heads encountered adjustment challenges related to unfamiliar environments, increased responsibilities, and changing stakeholder expectations. However, support from teachers, parents, local government units, and community stakeholders facilitated smoother transitions and strengthened school operations. Mobility enhanced leadership adaptability, resilience, collaboration, and professional growth, although temporary disruptions in continuity and relationship building were also experienced. Participants identified trust-building, inclusive leadership, collaboration, and emotional readiness as critical factors in managing successful transitions. Repeated mobility experiences increased confidence, leadership competence, and the capacity to respond effectively to diverse school contexts. The study concluded that school head mobility is both a leadership challenge and an opportunity for professional development and educational improvement. It recommends strengthening transition support, leadership development initiatives, mentoring programs, stakeholder collaboration, and succession planning mechanisms. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice and Strong Institutions) by promoting effective educational leadership, workforce development, and institutional continuity. The findings contribute to educational, institutional, community, and governance sustainability through strengthened leadership practices and stakeholder engagement.
Keywords: Adaptability; Leadership Continuity; Mobility; School Heads; Stakeholder Engagement; Succession Programs; Transformational Leadership; Transition Experiences